A high-temperature and high-density silicate water-based drilling fluid
Through reasonable formulation of high -temperature and high -density silicate water base drilling fluid, it solves the problem that the existing technology is difficult to meet multiple performance requirements under high temperature and high density conditions, and realizes the stability and safety of the well wall in the deep hard crispy shale formation. High -efficiency drilling.
Patent Information
- Application Number
- CN202411155395.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-08-22
AI Technical Summary
Existing silicate water-based drilling fluids are difficult to meet the requirements of rheology, filtration loss, sealing, lubrication, inhibition and anti-collapse performance under high temperature and high density conditions, especially in deep hard and brittle shale formations, resulting in well walls. Instability and collapse.
Provide a high -temperature and high -density silicate water base drilling solution, which is reasonably prepared for corpus soil, pH regulator, silicate, silicate stabilizer, anti -high -temperature flow variable regulator, anti -high temperature blocking filtration loss agent, Anti -high temperature decentralized inhibitors and lubricants are controlled at 1.80 ~ 2.30g/cm3 to ensure stability and performance under high temperature conditions.
The drilling solution shows good flow, filtering, blocking, lubricating, suppressing and collapse performance under high temperature and high density conditions, effectively prevent the loss and collapse of deep hard and brittle shale strata, and ensure the safety and efficiency of the drilling process. Essence
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drilling fluids, and in particular to a high-temperature and high-density silicate water-based drilling fluid. Background Art
[0002] As the global energy situation becomes increasingly complex, the fields of geological and energy exploration are deepening, oil and gas exploration is rapidly extending to deep and ultra-deep layers, and resource extraction types are also developing from conventional to unconventional. The development of deep oil and gas resources has become an important strategy for my country's oil and gas development. However, wellbore stability is the key to ensuring safe and efficient drilling. With the increase in drilling depth, especially in strong geostress tectonic formations and shale well sections, wellbore instability occurs frequently, becoming the main cause of well accidents.
[0003] Studies have shown that more than 90% of wellbore instability problems occur in mud shale layers and coal seams, which are usually related to the mechanical and physical and chemical interactions between drilling fluid and mud shale or coal seams. For shallow soft mud shale, wellbore instability caused by hydration expansion is particularly serious, especially for mud shale with high montmorillonite and chlorite content; while for coal seams, their structure, properties and geostress environment are the main factors. In high-temperature deep wells, the stability of hard and brittle shale formations with illite as the main mineral is still a problem. Due to its bedding and natural fractures, drilling fluid is prone to leakage and cause wellbore collapse.
[0004] High temperature and high pressure conditions pose a huge challenge to the performance of drilling fluids. Although traditional oil-based drilling fluids have greater advantages in temperature resistance, inhibition, lubricity and sealing properties, the high cost and high pollution problems they face are still difficult to solve. In contrast, water-based drilling fluids have greater development potential due to their low cost and good environmental protection. However, there are still some technical challenges in solving the instability problem of deep hard and brittle shale sections in existing water-based drilling fluids. Therefore, researchers have turned their attention to silicate drilling fluids, hoping to solve the stability problem of deep hard and brittle shale sections through the chemical wall-solidifying properties of silicates. Existing studies are as follows:
[0005] The invention patent "Deep Well High Temperature Resistant and Stable Well Wall Silicate Drilling Fluid" with application number CN02152375.4 discloses a deep well high temperature resistant and stable well wall silicate drilling fluid used in the oil field drilling field. It has strong temperature resistance and uses the cloud point effect of non-ionic surfactants to seal and protect the reservoir. It can inhibit the dispersion of cuttings, has strong ability to absorb water molecules, has good water loss reduction effect, improves drilling fluid viscosity and shear force, and has good stability of the well wall under high temperature conditions in deep wells. The silicate drilling fluid described in the invention can resist temperatures up to 180°C, but has a low density of no more than 1.10g / cm 3 .
[0006] The invention patent "A potassium silicate polyol water-based drilling fluid" with application number CN201110391281.4 discloses a potassium silicate polyol water-based drilling fluid for preventing collapse and stuck drilling in oil and gas field drilling operations. The drilling fluid has good rheological properties and water loss wall-forming properties at high temperatures, strong inhibition, strong plugging ability, good lubricity, and good thermal stability, and can meet the requirements of safe drilling in complex situations. However, the silicate drilling fluid described in the invention has a temperature resistance of only 150°C and a density of no more than 1.55g / cm 3 .
[0007] Application No. CN2018104806195 "A stabilizer for silicate drilling fluid, preparation method thereof, and silicate drilling fluid" discloses a stabilizer for silicate drilling fluid, preparation method thereof, and silicate drilling fluid. The silicate drilling fluid stabilizer of the invention can prevent solid phase particles such as clay and barite from reacting with silicates at high temperatures to cause drilling fluid thickening and increased water loss. The rheology and filtration loss of the drilling fluid can be easily controlled within a reasonable range, while reducing the amount of other types of treatment agents added to the drilling fluid. The silicate drilling fluid described in the invention has a density of up to 2.0 g / cm 3 , but the temperature resistance is low, only 120℃.
[0008] At present, the reports on silicate water-based drilling fluids in the published patents and scientific papers are either high temperature and low density or high density and low temperature. There are few theoretical studies and practical applications of high temperature and high density silicate water-based drilling fluids. Based on this, a high temperature and high density silicate water-based drilling fluid is studied and developed. On the one hand, it can adapt to the high temperature and high pressure formation environment at the same time, and meet the basic requirements of normal drilling for drilling fluid rheology, filtration loss, plugging, lubrication and inhibition performance; on the other hand, it can effectively solve the wellbore stability problem of hard and brittle shale formations dominated by illite, and ensure the safe and efficient drilling process, which has important practical significance for the development of deep oil and gas resources. Summary of the invention
[0009] The present invention provides a high-temperature and high-density silicate water-based drilling fluid to overcome the shortcomings of the existing silicate water-based drilling fluid technology and solve the problem of wellbore stability in deep hard and brittle shale formations. The drilling fluid has stable rheological, filtration, plugging, lubrication, inhibition and anti-collapse properties under high temperature and high density conditions, can effectively prevent the deep hard and brittle shale formations from becoming unstable and collapsing, and ensure the stability of the wellbore wall during the drilling process.
[0010] In order to achieve the above-mentioned object, the present invention provides the following technical scheme: a high-temperature and high-density silicate water-based drilling fluid, wherein the raw materials include, by weight, 100 parts of water, 1.0-2.0 parts of bentonite, 3.0-5.0 parts of pH regulator, 3.0-5.0 parts of silicate, 3.0-5.0 parts of silicate stabilizer, 0.1-0.3 parts of high-temperature rheology regulator, 4.0-6.0 parts of high-temperature plugging and filtration reducer, 2.0-3.0 parts of high-temperature dispersion inhibitor, 2.0-4.0 parts of lubricant and barite; the barite is not limited in number, and the density of the silicate water-based drilling fluid added is 1.80-2.30 g / cm 3 .
[0011] Preferably, the pH adjuster is at least one of potassium hydroxide, magnesium oxide and magnesium hydroxide.
[0012] Preferably, the silicate is at least one of potassium silicate, potassium methyl silicate and potassium phenyl silicate.
[0013] Preferably, the silicate stabilizer is at least one of potassium citrate, potassium ethylenediaminetetramethylenephosphonate, potassium hydroxyethylidene diphosphonate and potassium diethylenetriaminepentamethylenephosphonate.
[0014] Preferably, the high temperature resistant rheology regulator comprises the following raw materials in parts by mass: 100 parts of water, 1 to 3 parts of diutan gum, 1 to 3 parts of N,N-dimethylacrylamide, 2 to 5 parts of N-vinylpyrrolidone, 0.5 to 1.5 parts of 2-acryloyloxybutylsulfonic acid and 0.02 to 0.05 parts of potassium persulfate.
[0015] Preferably, the preparation method of the high temperature resistant rheology regulator comprises the following steps:
[0016] Dissolving diutan gum in water to obtain a diutan gum aqueous solution;
[0017] Adding 2-acryloyloxybutylsulfonic acid to the diutanol aqueous solution and adjusting the pH to alkaline to obtain a mixed solution I;
[0018] The mixed solution I is heated, and then N,N-dimethylacrylamide and N-vinylpyrrolidone are added in sequence under an inert atmosphere. After stirring evenly, potassium persulfate is added to initiate a polymerization reaction, thereby obtaining the high temperature resistant rheology regulator.
[0019] Preferably, the high temperature resistant plugging and filtration loss reducer comprises the following raw materials in parts by mass: 200 parts of methanol aqueous solution, 150 parts of water, 10-20 parts of nanocellulose crystals, 2-5 parts of vinyltrimethoxysilane, 1-3 parts of acrylamide, 3-5 parts of 2-acrylamide-2-methylpropanesulfonic acid, 0.05-0.10 parts of acetic acid and 0.05-0.08 parts of ammonium persulfate.
[0020] Preferably, the preparation method of the high temperature resistant plugging fluid loss reducer comprises the following steps:
[0021] Vinyltrimethoxysilane and acetic acid are added to a methanol aqueous solution to carry out a hydrolysis reaction. After the hydrolysis reaction is completed, nanocellulose crystals are added to the hydrolyzate to carry out a heating and stirring reaction to obtain an intermediate product A.
[0022] Mix water, acrylamide and 2-acrylamide-2-methylpropanesulfonic acid and adjust the pH to alkaline to obtain a mixed solution II;
[0023] The mixed solution II is stirred, and then the intermediate product A is added to the mixed solution II under stirring conditions, and then ammonium persulfate is added under the protection of an inert atmosphere to initiate a polymerization reaction, thereby obtaining the high temperature resistant plugging and filtration reducer.
[0024] Preferably, the high temperature resistant dispersion inhibitor comprises the following raw materials in parts by mass: 200 parts of ethanol aqueous solution, 150 parts of water, 40-80 parts of tannic acid, 2-4 parts of γ-methacryloxypropyltriethoxysilane, 3-5 parts of allylamine, 4-6 parts of methacrylamide, 5-8 parts of sodium styrene sulfonate and 0.10-0.16 parts of 2,2'-azobisisobutylamidine dihydrochloride.
[0025] Preferably, the method for preparing the high temperature resistant dispersion inhibitor comprises the following steps:
[0026] γ-methacryloxypropyltriethoxysilane is added to an ethanol aqueous solution, and then a hydrolysis reaction is carried out under acidic conditions. After the hydrolysis reaction is completed, tannic acid is added to the hydrolysis solution, and a heating and stirring reaction is carried out to obtain an intermediate product B;
[0027] After dissolving the intermediate product B in water, adjusting the pH to alkaline to obtain an aqueous solution of the intermediate product B;
[0028] The aqueous solution of the intermediate product B is stirred, and then allylamine, methacrylamide and sodium styrene sulfonate are added in sequence, and then 2,2'-azobisisobutylamidine dihydrochloride is added under the protection of an inert atmosphere to initiate a polymerization reaction to obtain the high temperature resistant dispersion inhibitor.
[0029] Beneficial technical effects
[0030] The high-temperature and high-density silicate water-based drilling fluid provided by the invention has a wider application range of density and temperature.
[0031] The high-temperature and high-density silicate water-based drilling fluid described in the present invention can maintain pH stability under high-temperature environment under the action of pH regulator, and combined with the role of silicate stabilizer in complexing high-valent cations such as calcium and magnesium, the stability of silicate under complex conditions is maintained, which provides a guarantee for the stability of drilling fluid performance. The compounding of inorganic silicate and organic silicate makes the drilling fluid not only have excellent cementation and anti-collapse performance, but also have excellent high-temperature stability, reducing the thermal degradation of the gel plugging layer formed by silicate under high-temperature environment, and improving the plugging effectiveness of drilling fluid in high-temperature deep wells; the hydrophobic film-forming properties of organic silicate also help to reduce the penetration of water into shale formations, ensuring the stability of deep shale formations. In addition, the anti-high-temperature rheological regulator, the anti-high-temperature plugging and filtration loss reducer, the anti-high-temperature dispersion inhibitor and lubricant mainly provide the drilling fluid with excellent high-temperature suspension stability, high-temperature filtration loss control, high-temperature and high-density rheological stability and high-temperature friction and torque reduction performance, further ensuring the effectiveness and reliability of the drilling fluid under high-temperature and high-density conditions.
[0032] The high-temperature and high-density silicate water-based drilling fluid provided by the present invention has stable and good rheological properties, filtration properties, plugging properties, lubrication properties, inhibition properties and anti-collapse properties, and can effectively solve the problem of wellbore stability in deep hard and brittle shale formations that conventional water-based drilling fluids cannot cope with, and meet the needs of safe and efficient drilling. DETAILED DESCRIPTION
[0033] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0034] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0035] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0036] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0037] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0038] The invention provides a high-temperature and high-density silicate water-based drilling fluid. The raw materials include, by weight, 100 parts of water, 1.0-2.0 parts of bentonite, 3.0-5.0 parts of pH regulator, 3.0-5.0 parts of silicate, 3.0-5.0 parts of silicate stabilizer, 0.1-0.3 parts of high-temperature rheology regulator, 4.0-6.0 parts of high-temperature plugging and filtration reducer, 2.0-3.0 parts of high-temperature dispersion inhibitor, 2.0-4.0 parts of lubricant and barite; the barite is not limited in number, and the density of the silicate water-based drilling fluid added is 1.80-2.30 g / cm 3 .
[0039] In some embodiments, the water is fresh water or sea water.
[0040] In some embodiments, the bentonite is commonly used in the drilling industry and can be obtained through commercial channels.
[0041] In some embodiments, the pH adjuster is at least one of potassium hydroxide, magnesium oxide and magnesium hydroxide.
[0042] In some embodiments, the pH regulator is a mixture of potassium hydroxide, magnesium oxide and magnesium hydroxide; based on 100 parts by mass, the pH regulator is composed of 30-40 parts of potassium hydroxide, 30-40 parts of magnesium oxide and 20-40 parts of magnesium hydroxide. In the present invention, the pH regulator is a compound of potassium hydroxide, magnesium oxide and magnesium hydroxide. Potassium hydroxide can provide a strong alkaline environment for the system. On the one hand, it ensures the stability of silicates. On the other hand, each component material can play the greatest role in an alkaline environment, and can also avoid acidic substances from corroding drilling tools. In addition, it also provides free potassium ions to improve the inhibition performance of drilling fluids; magnesium oxide and magnesium hydroxide can effectively alleviate the problem of too fast alkalinity drop in drilling fluids under high temperature conditions.
[0043] In some embodiments, the silicate is at least one of potassium silicate, potassium methyl silicate and potassium phenyl silicate.
[0044] In some embodiments, the silicate is a mixture of potassium silicate, methyl potassium silicate and phenyl potassium silicate; based on 100 parts by mass, the silicate consists of 40 to 60 parts of potassium silicate (modulus is 2.8 to 3.3), 20 to 30 parts of methyl potassium silicate and 20 to 30 parts of phenyl potassium silicate. In the present invention, the silicate is a compound of potassium silicate, methyl potassium silicate and phenyl potassium silicate. The silicate penetrates into the micropores and microcracks in the shale formation, and forms a high-strength gel through hydrolysis and condensation reaction, which is beneficial to cementing the well wall, thereby preventing collapse and block falling; at the same time, the high-valent mineral ions in the formation can also react with the silicate to form precipitation or gel, thereby strengthening the plugging effect of the micropores or microcracks, and achieving the purpose of stabilizing the well wall; furthermore, methyl silicate and phenyl silicate also have certain hydrophobic properties due to the methyl and phenyl groups, which are helpful to form a hydrophobic film, prevent further intrusion of water, and reduce the impact on clay minerals in the shale formation; in addition, the rigid structure of the benzene ring contained in the phenyl silicate can also provide protection for the silicon-oxygen bond in the gel structure, which is helpful to reduce thermal decomposition at high temperature and improve the temperature resistance of the gel plugging layer.
[0045] In some embodiments, the silicate stabilizer is at least one of potassium citrate, potassium ethylenediaminetetramethylenephosphonate, potassium hydroxyethylidene diphosphonate, and potassium diethylenetriaminepentamethylenephosphonate.
[0046] In some embodiments, the silicate stabilizer is a mixture of potassium citrate, potassium ethylenediaminetetramethylenephosphonate, potassium hydroxyethylidene diphosphonate and potassium diethylenetriamine penta methylenephosphonate; in parts by mass, the silicate stabilizer is composed of 30 to 40 parts of potassium citrate, 30 to 40 parts of potassium ethylenediaminetetramethylenephosphonate, 10 to 20 parts of potassium hydroxyethylidene diphosphonate and 10 to 20 parts of potassium diethylenetriamine penta methylenephosphonate. In the present invention, the silicate stabilizer is a composite of potassium citrate, potassium ethylenediaminetetramethylenephosphonate, potassium hydroxyethylidene diphosphonate and potassium diethylenetriamine penta methylenephosphonate. On the one hand, potassium citrate, potassium ethylenediaminetetramethylenephosphonate, potassium hydroxyethylidene diphosphonate and potassium diethylenetriamine penta methylenephosphonate can provide potassium ions and amino groups, which are helpful to strengthen the inhibition of drilling fluid; on the other hand, citrate and organic phosphonate can complex high-valent ions such as calcium and magnesium in water, which is beneficial to the stability of silicate in the system.
[0047] In some embodiments, the high temperature resistant rheology modifier is a diutan gum graft copolymer, comprising the following raw materials in parts by weight: 100 parts of water, 1 to 3 parts of diutan gum, 1 to 3 parts of N, N-dimethylacrylamide, 2 to 5 parts of N-vinyl pyrrolidone, 0.5 to 1.5 parts of 2-acryloyloxybutyl sulfonic acid and 0.02 to 0.05 parts of potassium persulfate.
[0048] It is particularly noted that the high temperature resistant rheology regulator is a polymer obtained by chemically modifying diutan gum, which itself is a microbial polysaccharide with good viscosity-increasing properties. The purpose of chemical modification is to improve its water-soluble dispersibility and temperature resistance so that it can meet the needs of high-temperature deep well operations. The diutan gum molecular chain contains a large number of hydroxyl and carboxyl groups. After chemical modification, molecular side chains containing amide groups, rigid five-membered rings and sulfonic acid groups are added. These side chains have extremely strong hydrophilicity and adsorption properties. On the one hand, they can enhance the water-soluble dispersibility of the polymer, and on the other hand, they can strengthen its interaction with sodium bentonite, greatly increase the temperature required for desorption, and help improve the temperature resistance; furthermore, the rigid five-membered ring and sulfonic acid group can also protect the main chain of the diutan gum molecule, reduce its thermal degradation at high temperatures, and further improve the temperature resistance.
[0049] In some embodiments, the preparation method of the high temperature resistant rheology modifier comprises the following steps:
[0050] Dissolving diutan gum in water to obtain a diutan gum aqueous solution;
[0051] Adding 2-acryloyloxybutylsulfonic acid to the diutanol aqueous solution and adjusting the pH to alkaline to obtain a mixed solution I;
[0052] The mixed solution I is heated, and then N,N-dimethylacrylamide and N-vinylpyrrolidone are added in sequence under an inert atmosphere. After stirring evenly, potassium persulfate is added to initiate a polymerization reaction, thereby obtaining the high temperature resistant rheology regulator.
[0053] In some embodiments, the present invention further comprises a step of heating the water before dissolving diutanol in water; the heating step is heating to 50°C.
[0054] In some embodiments, the specific operation of dissolving diutanol in water to obtain a diutanol aqueous solution is: heating deionized water to 50° C., and then slowly adding diutanol under stirring conditions.
[0055] In some embodiments, after adding 2-acryloyloxybutylsulfonic acid to the diutanol aqueous solution, the pH is adjusted to alkaline, and the pH is adjusted to alkaline by using 0.1 mol / L sodium hydroxide aqueous solution to adjust the pH to 7-8.
[0056] In some embodiments, heating the mixed solution I is heating the mixed solution I to 60-80°C.
[0057] In some embodiments, potassium persulfate is added to initiate the polymerization reaction, the polymerization reaction temperature is 60-80°C, and the time is 3-6h; after the polymerization reaction is completed, the process further includes cooling to room temperature, precipitating the reaction product with acetone, and sequentially drying and crushing the obtained precipitate; the drying is vacuum drying at 50°C.
[0058] In some embodiments, the high temperature resistant plugging and filtration loss reducer is a nanocellulose derivative, comprising the following raw materials in parts by weight: 200 parts of methanol aqueous solution, 150 parts of water, 10 to 20 parts of nanocellulose crystals, 2 to 5 parts of vinyltrimethoxysilane, 1 to 3 parts of acrylamide, 3 to 5 parts of 2-acrylamide-2-methylpropane sulfonic acid, 0.05 to 0.10 parts of acetic acid and 0.05 to 0.08 parts of ammonium persulfate.
[0059] Nanocellulose crystals are a type of nanomaterial with good fluid loss reduction performance, but their water solubility and temperature resistance limit their application in high-temperature water-based drilling fluids. The high-temperature resistant fluid loss reducer is a nanocellulose derivative obtained by chemically modifying nanocellulose crystals, which significantly improves its water solubility and temperature resistance. By introducing a large number of hydrophilic groups, such as amide groups, sulfonic acid groups, etc., it is beneficial to improve the water solubility and dispersibility of the material, and can strengthen its interaction with sodium bentonite, which is beneficial to the formation of a denser mud cake, thereby improving the plugging and fluid loss reduction performance; in addition, the Si-O bonds and sulfonic acid groups contained in the fluid loss reducer molecular chain enhance its temperature resistance, so that it can still play an excellent role in fluid loss reduction at high temperatures.
[0060] In some embodiments, the concentration of methanol in the methanol aqueous solution is 90% (v / v).
[0061] In some embodiments, the preparation method of the high temperature resistant plugging fluid loss reducer comprises the following steps:
[0062] Vinyltrimethoxysilane and acetic acid are added to a methanol aqueous solution to carry out a hydrolysis reaction. After the hydrolysis reaction is completed, nanocellulose crystals are added to the hydrolyzate to carry out a heating and stirring reaction to obtain an intermediate product A.
[0063] Mix water, acrylamide and 2-acrylamide-2-methylpropanesulfonic acid and adjust the pH to alkaline to obtain a mixed solution II;
[0064] The mixed solution II is stirred, and then the intermediate product A is added to the mixed solution II under stirring conditions, and then ammonium persulfate is added under the protection of an inert atmosphere to initiate a polymerization reaction, thereby obtaining the high temperature resistant plugging and filtration reducer.
[0065] In some embodiments, vinyltrimethoxysilane and acetic acid are added to a methanol aqueous solution for hydrolysis reaction, and the temperature of the hydrolysis reaction is 55° C. and the time is 5 hours.
[0066] In some embodiments, nanocellulose crystals are added to the hydrolyzate to carry out a heating and stirring reaction, the reaction temperature of the heating and stirring reaction is 75-85°C, and the reaction time is 16-24h; after the heating and stirring reaction is completed, the steps of cooling to room temperature, centrifuging to remove the solvent, washing, and drying are also included; the solution used for washing is anhydrous methanol; the drying method is vacuum drying.
[0067] In some embodiments, water, acrylamide and 2-acrylamide-2-methylpropanesulfonic acid are mixed and then the pH is adjusted to alkaline, and the pH is adjusted to alkaline by using 0.1 mol / L sodium hydroxide aqueous solution to adjust the pH to 7-8.
[0068] In some embodiments, the mixed solution II is stirred for 10-30 min.
[0069] In some embodiments, ammonium persulfate is added to initiate the polymerization reaction, the polymerization reaction temperature is 60-70°C, and the time is 3-6h; after the polymerization reaction is completed, the steps of cooling to room temperature, washing, filtering, drying and crushing are also included; the washing is performed using distilled water; the filtering method is suction filtration; the drying method is vacuum drying.
[0070] In some embodiments, the high temperature resistant dispersion inhibitor is a tannic acid derivative, comprising the following raw materials in parts by weight: 200 parts of ethanol aqueous solution, 150 parts of water, 40-80 parts of tannic acid, 2-4 parts of γ-methacryloxypropyltriethoxysilane, 3-5 parts of allylamine, 4-6 parts of methacrylamide, 5-8 parts of sodium styrene sulfonate and 0.10-0.16 parts of 2,2'-azobisisobutylamidine dihydrochloride.
[0071] It is particularly noted that the high temperature resistant dispersant is a polymer obtained by chemical modification on the basis of tannic acid, and tannic acid itself is a good drilling fluid dispersant with good viscosity reduction performance. The purpose of chemical modification is to improve its temperature resistance and inhibition performance so that it can meet the needs of deep shale formation drilling operations. Tannic acid molecular chains contain a large number of hydroxyl groups and carboxyl groups. After chemical modification, molecular side chains containing amino groups, amide groups and sulfonic acid groups are added. These multi-functional side chains give the polymer extremely strong hydrophilicity and adsorption. On the one hand, they can strengthen its adsorption of solid phase weighting materials and reduce the internal friction between solid phase particles, thereby playing a role in reducing the plastic viscosity of the drilling fluid; on the other hand, they also have a certain inhibitory property, which can effectively prevent the hydration of clay minerals and is beneficial to the stability of shale well walls. In addition, the molecular side chain is connected to the main chain of the tannic acid molecule through a Si-O bond, and under the synergistic effect of the sulfonic acid group, the heat resistance is significantly improved.
[0072] In some embodiments, the concentration of ethanol in the ethanol aqueous solution is 90% (v / v).
[0073] In some embodiments, the method for preparing the high temperature resistant dispersion inhibitor comprises the following steps:
[0074] γ-methacryloxypropyltriethoxysilane is added to an ethanol aqueous solution, and then a hydrolysis reaction is carried out under acidic conditions. After the hydrolysis reaction is completed, tannic acid is added to the hydrolysis solution, and a heating and stirring reaction is carried out to obtain an intermediate product B;
[0075] After dissolving the intermediate product B in water, adjusting the pH to alkaline to obtain an aqueous solution of the intermediate product B;
[0076] The aqueous solution of the intermediate product B is stirred, and then allylamine, methacrylamide and sodium styrene sulfonate are added in sequence, and then 2,2'-azobisisobutylamidine dihydrochloride is added under the protection of an inert atmosphere to initiate a polymerization reaction to obtain the high temperature resistant dispersion inhibitor.
[0077] In some embodiments, γ-methacryloxypropyltriethoxysilane is added to an ethanol aqueous solution, and then a hydrolysis reaction is carried out under acidic conditions. The specific operation is as follows: γ-methacryloxypropyltriethoxysilane is added to an ethanol aqueous solution, the pH is adjusted to 3-5 with citric acid, and then a hydrolysis reaction is carried out under stirring conditions; the temperature of the hydrolysis reaction is 50° C., and the time is 3 hours.
[0078] In some embodiments, tannic acid is added to the hydrolysis solution for a heating and stirring reaction, the temperature of the heating and stirring reaction is 65-75°C, and the time is 12-20 hours; after the heating and stirring reaction is completed, it also includes cooling to room temperature, centrifuging to remove the solvent, washing, drying and crushing steps; the solution used for washing is anhydrous ethanol; the drying method is vacuum drying.
[0079] In some embodiments, the intermediate product B is dissolved in water and then the pH is adjusted to alkaline, and the pH adjustment to alkaline is specifically to adjust the pH to 7-8 with 0.1 mol / L sodium hydroxide solution.
[0080] In some embodiments, the aqueous solution of the intermediate product B is stirred for 30 minutes.
[0081] In some embodiments, 2,2'-azobisisobutylamidine dihydrochloride is added to initiate the polymerization reaction under the protection of an inert atmosphere, the polymerization reaction temperature is 65-75°C, and the time is 3-5h; after the polymerization reaction is completed, the steps of cooling to room temperature, washing, drying and crushing are also included.
[0082] In some embodiments, the lubricant is a liquid lubricant and / or a solid lubricant.
[0083] In some embodiments, the lubricant is a mixture of a liquid lubricant and a solid lubricant; based on 100 parts by mass, the lubricant consists of 80-90 parts of liquid lubricant and 10-20 parts of solid lubricant.
[0084] In some embodiments, the liquid lubricant is a mixture of polydimethylsiloxane, trimethylolpropane esterified rapeseed oil, phosphated palm oil and polyoxyethylene laurate; based on 100 parts by mass, the liquid lubricant consists of 30 to 40 parts of polydimethylsiloxane, 20 to 30 parts of trimethylolpropane esterified rapeseed oil, 15 to 25 parts of phosphated palm oil and 15 to 25 parts of polyoxyethylene laurate.
[0085] In some embodiments, the solid lubricant is a mixture of molybdenum disulfide powder, polytetrafluoroethylene powder, boron nitride powder and carbon nanotubes; based on 100 parts by mass, the solid lubricant consists of 30 to 40 parts of molybdenum disulfide powder, 30 to 40 parts of polytetrafluoroethylene powder, 10 to 20 parts of boron nitride powder and 10 to 20 parts of carbon nanotubes.
[0086] The high-temperature and high-density silicate water-based drilling fluid provided by the present invention can be prepared by a conventional preparation method.
[0087] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0088] Unless otherwise specified, the raw materials and reagents used in the examples can be obtained through commercial sources.
[0089] The bentonite described in the examples is a commonly used bentonite in the drilling industry and is commercially available.
[0090] The high-temperature and high-density silicate water-based drilling fluid in the embodiment is obtained by uniformly mixing various components. Example 1
[0091] This embodiment provides a high-temperature, high-density silicate water-based drilling fluid, which is composed of the following components in parts by weight:
[0092] Fresh water: 100 parts
[0093] Bentonite: 1.0 part
[0094] pH adjuster: 3.0 parts
[0095] Silicate: 3.0 parts
[0096] Silicate stabilizer: 3.0 parts
[0097] High temperature resistant rheology modifier: 0.1 part
[0098] High temperature resistant plugging and filtration reducer: 4.0 parts
[0099] High temperature resistant dispersion inhibitor: 2.0 parts
[0100] Lubricant: 2.0 parts
[0101] Barite: Add to drilling fluid to a density of 2.30 g / cm 3 .
[0102] Wherein, the pH regulator is a mixture of 30 parts of potassium hydroxide, 30 parts of magnesium oxide and 40 parts of magnesium hydroxide by mass;
[0103] The silicate is a mixture of 40 parts of potassium silicate (modulus 2.8), 30 parts of potassium methyl silicate and 30 parts of potassium phenyl silicate by mass;
[0104] The silicate stabilizer is a mixture of 30 parts of potassium citrate, 30 parts of potassium ethylenediaminetetramethylenephosphonate, 20 parts of potassium hydroxyethylidene diphosphonate and 20 parts of potassium diethylenetriaminepentamethylenephosphonate by mass;
[0105] The high temperature resistant rheology modifier is a diutan gum graft copolymer, which is prepared from the following raw materials in parts by weight: 100 parts of deionized water, 1 part of diutan gum, 1 part of N,N-dimethylacrylamide, 2 parts of N-vinyl pyrrolidone, 0.5 parts of 2-acryloyloxybutyl sulfonic acid, and 0.02 parts of potassium persulfate;
[0106] The preparation method of the diutan gum graft copolymer comprises the following steps:
[0107] First, deionized water is heated to 50°C, and then diutanol is slowly added under stirring. After it is fully dissolved, the diutanol aqueous solution is transferred to a four-necked round-bottom flask, 2-acryloxybutylsulfonic acid is added thereto, and the pH of the mixed solution is adjusted to 7 with a 0.1 mol / L sodium hydroxide aqueous solution; then, after the temperature is raised to 60°C, nitrogen is introduced for deoxygenation, and N,N-dimethylacrylamide and N-vinylpyrrolidone are added in sequence. After stirring for 1 hour, potassium persulfate is added to initiate the polymerization reaction, which is continued for 3 hours, and the reaction is stopped and cooled to room temperature; then, the reaction product is precipitated with acetone, and vacuum dried at 50°C, and the dried product is crushed to obtain the target product.
[0108] The high temperature resistant plugging and filtration reducer is a nanocellulose derivative, which is prepared from the following raw materials in parts by weight: 200 parts of 90% (v / v) methanol aqueous solution, 150 parts of deionized water, 10 parts of nanocellulose crystals, 2 parts of vinyltrimethoxysilane, 1 part of acrylamide, 3 parts of 2-acrylamide-2-methylpropanesulfonic acid, 0.05 parts of acetic acid, and 0.05 parts of ammonium persulfate;
[0109] The above-mentioned method for preparing the nanocellulose derivative comprises the following steps:
[0110] First, vinyltrimethoxysilane and acetic acid were added to a four-necked round-bottom flask filled with 90% (v / v) methanol aqueous solution, and then the temperature was slowly raised to 55°C under stirring conditions, and the hydrolysis reaction was carried out for 5 hours; then nanocellulose crystals were slowly added, and the temperature was continuously raised to 75°C under stirring. After the reaction was carried out for 16 hours, the heating was stopped and the product was cooled to room temperature; the solvent was removed by centrifugation, and the product was washed with anhydrous methanol for several times, and then vacuum dried to obtain the intermediate product;
[0111] Secondly, deionized water, acrylamide and 2-acrylamide-2-methylpropanesulfonic acid were added to a four-necked round-bottom flask in sequence, and the pH was adjusted to 7 with a 0.1 mol / L sodium hydroxide aqueous solution and stirred for 10 minutes; then, the intermediate product obtained in the above step was added thereto under stirring, nitrogen was passed for deoxygenation, the temperature was raised to 60°C, and ammonium persulfate was added to initiate the polymerization reaction, which lasted for 3 hours, then the reaction was stopped and cooled to room temperature; then, the mixture was washed with distilled water for multiple times, vacuum filtered, vacuum dried and crushed, and the obtained product was a nanocellulose derivative.
[0112] The high temperature resistant dispersion inhibitor is a tannic acid derivative, which is prepared from the following raw materials in parts by mass: 200 parts of 90% (v / v) ethanol aqueous solution, 150 parts of deionized water, 40 parts of tannic acid, 2 parts of γ-methacryloxypropyltriethoxysilane, 3 parts of allylamine, 4 parts of methacrylamide, 5 parts of sodium styrene sulfonate, and 0.10 parts of 2,2'-azobisisobutylamidine dihydrochloride;
[0113] The above-mentioned method for preparing tannic acid derivatives comprises the following steps:
[0114] First, γ-methacryloxypropyltriethoxysilane was added to a four-necked round-bottom flask filled with 90% (v / v) ethanol aqueous solution, and the pH was adjusted to 3 with citric acid, and then the temperature was slowly raised to 50°C under stirring conditions, and the hydrolysis reaction was carried out for 3 hours; then tannic acid was slowly added, and the temperature was continuously raised to 65°C with stirring, and the heating was stopped after the reaction for 12 hours, and the solution was cooled to room temperature; the solvent was removed by centrifugation, and the solution was washed with anhydrous ethanol for multiple times, and then vacuum dried and crushed to obtain an intermediate product;
[0115] Secondly, the intermediate product is added into a four-necked round-bottom flask filled with deionized water, and the pH is adjusted to 7 with 0.1 mol / L sodium hydroxide solution. After stirring for 30 minutes, allylamine, methacrylamide and sodium styrene sulfonate are added in sequence, nitrogen is passed to deoxygenate, and after heating to 65°C, 2,2'-azobisisobutylamidine dihydrochloride is added to initiate the polymerization reaction, which is continued for 3 hours. After the reaction is completed, the mixture is cooled to room temperature, and a tannic acid derivative is obtained by washing, drying and crushing.
[0116] The lubricant is a mixture of 80 parts of liquid lubricant and 20 parts of solid lubricant by mass; wherein, the liquid lubricant is a mixture of 30 parts of polydimethylsiloxane, 20 parts of trimethylolpropane esterified rapeseed oil, 25 parts of phosphated palm oil and 25 parts of polyoxyethylene laurate by mass; the solid lubricant is a mixture of 30 parts of molybdenum disulfide micropowder, 30 parts of polytetrafluoroethylene micropowder, 20 parts of boron nitride micropowder and 20 parts of carbon nanotubes.
[0117] The density of the drilling fluid in this embodiment is 2.30 g / cm 3 The hot rolling temperature of the drilling fluid is 150℃. Example 2
[0118] This embodiment provides a high-temperature, high-density silicate water-based drilling fluid, which is composed of the following components in parts by weight:
[0119] Fresh water: 100 parts
[0120] Bentonite: 1.5 parts
[0121] pH adjuster: 4.0 parts
[0122] Silicate: 4.0 parts
[0123] Silicate stabilizer: 4.0 parts
[0124] High temperature resistant rheology modifier: 0.2 parts
[0125] High temperature resistant plugging and filtration reducer: 5.0 parts
[0126] High temperature resistant dispersion inhibitor: 2.0 parts
[0127] Lubricant: 3.0 parts
[0128] Barite: Add to drilling fluid to a density of 2.05 g / cm 3 .
[0129] Wherein, the pH regulator is a mixture of 35 parts of potassium hydroxide, 35 parts of magnesium oxide and 30 parts of magnesium hydroxide by mass;
[0130] The silicate is a mixture of 50 parts of potassium silicate (modulus 3.05), 25 parts of methyl potassium silicate and 25 parts of phenyl potassium silicate by mass;
[0131] The silicate stabilizer is a mixture of 35 parts of potassium citrate, 35 parts of potassium ethylenediaminetetramethylenephosphonate, 15 parts of potassium hydroxyethylidene diphosphonate and 15 parts of potassium diethylenetriaminepentamethylenephosphonate by mass;
[0132] The high temperature resistant rheology modifier is a diutan gum graft copolymer, which is prepared from the following raw materials in parts by weight: 100 parts of deionized water, 2 parts of diutan gum, 2 parts of N,N-dimethylacrylamide, 3.5 parts of N-vinylpyrrolidone, 1.0 parts of 2-acryloyloxybutylsulfonic acid, and 0.035 parts of potassium persulfate;
[0133] The preparation method of the diutan gum graft copolymer comprises the following steps:
[0134] First, deionized water is heated to 50°C, and then diutanol is slowly added under stirring. After it is fully dissolved, the diutanol aqueous solution is transferred to a four-necked round-bottom flask, 2-acryloyloxybutylsulfonic acid is added thereto, and the pH of the mixed solution is adjusted to 7.5 with a 0.1 mol / L sodium hydroxide aqueous solution; subsequently, the temperature is raised to 70°C, nitrogen is introduced for deoxygenation, and N,N-dimethylacrylamide and N-vinylpyrrolidone are added in sequence. After stirring for 1.5 hours, potassium persulfate is added to initiate the polymerization reaction, which is continued for 4.5 hours, and the reaction is stopped and cooled to room temperature; then, the reaction product is precipitated with acetone, and vacuum dried at 50°C, and the dried product is crushed to obtain the target product.
[0135] The high temperature resistant plugging and filtration reducer is a nanocellulose derivative, which is prepared from the following raw materials in parts by weight: 200 parts of 90% (v / v) methanol aqueous solution, 150 parts of deionized water, 15 parts of nanocellulose crystals, 3.5 parts of vinyltrimethoxysilane, 2 parts of acrylamide, 4 parts of 2-acrylamide-2-methylpropanesulfonic acid, 0.075 parts of acetic acid, and 0.065 parts of ammonium persulfate;
[0136] The above-mentioned method for preparing the nanocellulose derivative comprises the following steps:
[0137] First, vinyltrimethoxysilane and acetic acid were added to a four-necked round-bottom flask filled with 90% (v / v) methanol aqueous solution, and then the temperature was slowly raised to 55°C under stirring conditions, and the hydrolysis reaction was carried out for 5 hours; then nanocellulose crystals were slowly added, and the temperature was raised to 80°C while stirring continuously. After the reaction was carried out for 20 hours, the heating was stopped and the product was cooled to room temperature; the solvent was removed by centrifugation, and the product was washed with anhydrous methanol for several times, and then vacuum dried to obtain the intermediate product;
[0138] Secondly, deionized water, acrylamide and 2-acrylamide-2-methylpropanesulfonic acid were added to a four-necked round-bottom flask in sequence, and the pH was adjusted to 7.5 with a 0.1 mol / L sodium hydroxide aqueous solution and stirred for 20 minutes; then, the intermediate product obtained in the above step was added thereto under stirring, nitrogen was passed for deoxygenation, the temperature was raised to 65°C, and ammonium persulfate was added to initiate the polymerization reaction, which lasted for 4.5 hours, then the reaction was stopped and cooled to room temperature; then, the mixture was washed with distilled water for multiple times, vacuum filtered, vacuum dried and crushed, and the obtained product was a nanocellulose derivative.
[0139] The high temperature resistant dispersion inhibitor is a tannic acid derivative, which is prepared from the following raw materials in parts by mass: 200 parts of 90% (v / v) ethanol aqueous solution, 150 parts of deionized water, 60 parts of tannic acid, 3 parts of γ-methacryloxypropyltriethoxysilane, 4 parts of allylamine, 5 parts of methacrylamide, 6.5 parts of sodium styrene sulfonate, and 0.13 parts of 2,2'-azobisisobutylamidine dihydrochloride;
[0140] The above-mentioned method for preparing tannic acid derivatives comprises the following steps:
[0141] First, γ-methacryloxypropyltriethoxysilane was added to a four-necked round-bottom flask filled with 90% (v / v) ethanol aqueous solution, and the pH was adjusted to 4 with citric acid, and then the temperature was slowly raised to 50°C under stirring conditions, and the hydrolysis reaction was carried out for 3 hours; then tannic acid was slowly added, and the temperature was continuously raised to 70°C with stirring, and the heating was stopped after the reaction for 16 hours, and the solution was cooled to room temperature; the solvent was removed by centrifugation, and the solution was washed with anhydrous ethanol for multiple times, and then vacuum dried and crushed to obtain an intermediate product;
[0142] Secondly, the intermediate product is added into a four-necked round-bottom flask filled with deionized water, and the pH is adjusted to 7.5 with 0.1 mol / L sodium hydroxide solution. After stirring for 30 minutes, allylamine, methacrylamide and sodium styrene sulfonate are added in sequence, nitrogen is passed to deoxygenate, and after heating to 70°C, 2,2'-azobisisobutylamidine dihydrochloride is added to initiate the polymerization reaction, which is continued for 4 hours. After the reaction is completed, the mixture is cooled to room temperature, and a tannic acid derivative is obtained by washing, drying and crushing.
[0143] The lubricant is a mixture of 85 parts of liquid lubricant and 15 parts of solid lubricant by mass; wherein, the liquid lubricant is a mixture of 35 parts of polydimethylsiloxane, 25 parts of trimethylolpropane esterified rapeseed oil, 20 parts of phosphated palm oil and 20 parts of polyoxyethylene laurate by mass; the solid lubricant is a mixture of 35 parts of molybdenum disulfide micropowder, 35 parts of polytetrafluoroethylene micropowder, 15 parts of boron nitride micropowder and 15 parts of carbon nanotubes.
[0144] The density of the drilling fluid in this embodiment is 2.05 g / cm 3 The hot rolling temperature of the drilling fluid is 175℃. Example 3
[0145] This embodiment provides a high-temperature, high-density silicate water-based drilling fluid, which is composed of the following components in parts by weight:
[0146] Fresh water: 100 parts
[0147] Bentonite: 2.0 parts
[0148] pH adjuster: 5.0 parts
[0149] Silicate: 5.0 parts
[0150] Silicate stabilizer: 5.0 parts
[0151] High temperature resistant rheology modifier: 0.3 parts
[0152] High temperature resistant plugging and filtration reducer: 6.0 parts
[0153] High temperature resistant dispersion inhibitor: 3.0 parts
[0154] Lubricant: 4.0 parts
[0155] Barite: Add to drilling fluid to a density of 1.80 g / cm 3 .
[0156] Wherein, the pH regulator is a mixture of 40 parts of potassium hydroxide, 40 parts of magnesium oxide and 20 parts of magnesium hydroxide by mass;
[0157] The silicate is a mixture of 60 parts of potassium silicate (modulus 3.3), 20 parts of methyl potassium silicate and 20 parts of phenyl potassium silicate by mass;
[0158] The silicate stabilizer is a mixture of 40 parts of potassium citrate, 40 parts of potassium ethylenediaminetetramethylenephosphonate, 10 parts of potassium hydroxyethylidene diphosphonate and 10 parts of potassium diethylenetriaminepentamethylenephosphonate by mass;
[0159] The high temperature resistant rheology modifier is a diutan gum graft copolymer, which is prepared from the following raw materials in parts by weight: 100 parts of deionized water, 3 parts of diutan gum, 3 parts of N,N-dimethylacrylamide, 5 parts of N-vinyl pyrrolidone, 1.5 parts of 2-acryloyloxybutyl sulfonic acid, and 0.05 parts of potassium persulfate;
[0160] The preparation method of the diutan gum graft copolymer comprises the following steps:
[0161] First, deionized water is heated to 50°C, and then diutanol is slowly added under stirring. After it is fully dissolved, the diutanol aqueous solution is transferred to a four-necked round-bottom flask, 2-acryloxybutylsulfonic acid is added thereto, and the pH of the mixed solution is adjusted to 8 with a 0.1 mol / L sodium hydroxide aqueous solution; subsequently, the temperature is raised to 80°C, nitrogen is introduced for deoxygenation, and N,N-dimethylacrylamide and N-vinylpyrrolidone are added in sequence. After stirring for 2 hours, potassium persulfate is added to initiate the polymerization reaction, which is continued for 6 hours, and the reaction is stopped and cooled to room temperature; then, the reaction product is precipitated with acetone, and vacuum dried at 50°C, and the dried product is crushed to obtain the target product.
[0162] The high temperature resistant plugging and filtration reducer is a nanocellulose derivative, which is prepared from the following raw materials in parts by weight: 200 parts of 90% (v / v) methanol aqueous solution, 150 parts of deionized water, 20 parts of nanocellulose crystals, 5 parts of vinyltrimethoxysilane, 3 parts of acrylamide, 5 parts of 2-acrylamide-2-methylpropanesulfonic acid, 0.10 parts of acetic acid, and 0.08 parts of ammonium persulfate;
[0163] The above-mentioned method for preparing the nanocellulose derivative comprises the following steps:
[0164] First, vinyltrimethoxysilane and acetic acid were added to a four-necked round-bottom flask filled with 90% (v / v) methanol aqueous solution, and then the temperature was slowly raised to 55°C under stirring conditions, and the hydrolysis reaction was carried out for 5 hours; then nanocellulose crystals were slowly added, and the temperature was raised to 85°C while stirring continuously. After reacting for 24 hours, the heating was stopped and the product was cooled to room temperature; the solvent was removed by centrifugation, and the product was washed with anhydrous methanol for several times, and then vacuum dried to obtain the intermediate product;
[0165] Secondly, deionized water, acrylamide and 2-acrylamide-2-methylpropanesulfonic acid were added to a four-necked round-bottom flask in sequence, and the pH was adjusted to 8 with a 0.1 mol / L sodium hydroxide aqueous solution and stirred for 30 minutes; then, the intermediate product obtained in the above step was added thereto under stirring, nitrogen was passed for deoxygenation, the temperature was raised to 70°C, and ammonium persulfate was added to initiate the polymerization reaction, which lasted for 6 hours, then the reaction was stopped and cooled to room temperature; then, the mixture was washed with distilled water for multiple times, vacuum filtered, vacuum dried and crushed, and the obtained product was a nanocellulose derivative.
[0166] The high temperature resistant dispersion inhibitor is a tannic acid derivative, which is prepared from the following raw materials in parts by mass: 200 parts of 90% (v / v) ethanol aqueous solution, 150 parts of deionized water, 80 parts of tannic acid, 4 parts of γ-methacryloxypropyltriethoxysilane, 5 parts of allylamine, 6 parts of methacrylamide, 8 parts of sodium styrene sulfonate, and 0.16 parts of 2,2'-azobisisobutylamidine dihydrochloride;
[0167] The above-mentioned method for preparing tannic acid derivatives comprises the following steps:
[0168] First, γ-methacryloxypropyltriethoxysilane was added to a four-necked round-bottom flask filled with 90% (v / v) ethanol aqueous solution, and the pH was adjusted to 5 with citric acid, and then the temperature was slowly raised to 50°C under stirring conditions, and the hydrolysis reaction was carried out for 3 hours; then tannic acid was slowly added, and the temperature was continuously raised to 75°C under stirring, and the heating was stopped after the reaction for 20 hours, and the solution was cooled to room temperature; the solvent was removed by centrifugation, and the solution was washed with anhydrous ethanol for multiple times, and then vacuum dried and crushed to obtain an intermediate product;
[0169] Secondly, the intermediate product is added into a four-necked round-bottom flask filled with deionized water, and the pH is adjusted to 8 with 0.1 mol / L sodium hydroxide solution. After stirring for 30 minutes, allylamine, methacrylamide and sodium styrene sulfonate are added in sequence, nitrogen is passed to deoxygenate, and after heating to 75°C, 2,2'-azobisisobutylamidine dihydrochloride is added to initiate the polymerization reaction, which is continued for 5 hours. After the reaction is completed, the mixture is cooled to room temperature, and a tannic acid derivative is obtained by washing, drying and crushing.
[0170] The lubricant is a mixture of 90 parts of liquid lubricant and 10 parts of solid lubricant by mass; wherein, the liquid lubricant is a mixture of 40 parts of polydimethylsiloxane, 30 parts of trimethylolpropane esterified rapeseed oil, 15 parts of phosphated palm oil and 15 parts of polyoxyethylene laurate by mass; the solid lubricant is a mixture of 40 parts of molybdenum disulfide micropowder, 40 parts of polytetrafluoroethylene micropowder, 10 parts of boron nitride micropowder and 10 parts of carbon nanotubes.
[0171] The density of the drilling fluid in this embodiment is 1.80 g / cm 3The hot rolling temperature of the drilling fluid is 200℃. Example 4
[0172] This embodiment provides a high-temperature, high-density silicate water-based drilling fluid, which is composed of the following components in parts by weight:
[0173] Fresh water: 100 parts
[0174] Bentonite: 2.0 parts
[0175] pH adjuster: 3.0 parts
[0176] Silicate: 3.0 parts
[0177] Silicate stabilizer: 5.0 parts
[0178] High temperature resistant rheology modifier: 0.1 part
[0179] High temperature resistant plugging and filtration reducer: 5.0 parts
[0180] High temperature resistant dispersion inhibitor: 3.0 parts
[0181] Lubricant: 3.0 parts
[0182] Barite: Add to drilling fluid to a density of 2.30 g / cm 3 .
[0183] Wherein, the pH regulator is a mixture of 35 parts of potassium hydroxide, 30 parts of magnesium oxide and 35 parts of magnesium hydroxide by mass;
[0184] The silicate is a mixture of 45 parts of potassium silicate (modulus 3.05), 30 parts of methyl potassium silicate and 25 parts of phenyl potassium silicate by mass;
[0185] The silicate stabilizer is a mixture of 40 parts of potassium citrate, 30 parts of potassium ethylenediaminetetramethylenephosphonate, 10 parts of potassium hydroxyethylidene diphosphonate and 20 parts of potassium diethylenetriaminepentamethylenephosphonate by mass;
[0186] The high temperature resistant rheology modifier is a diutan gum graft copolymer, which is prepared from the following raw materials in parts by weight: 100 parts of deionized water, 1 part of diutan gum, 3 parts of N,N-dimethylacrylamide, 2 parts of N-vinyl pyrrolidone, 1.0 part of 2-acryloyloxybutyl sulfonic acid, and 0.03 parts of potassium persulfate;
[0187] The preparation method of the diutan gum graft copolymer comprises the following steps:
[0188] First, deionized water is heated to 50°C, and then diutanol is slowly added under stirring. After it is fully dissolved, the diutanol aqueous solution is transferred to a four-necked round-bottom flask, 2-acryloxybutylsulfonic acid is added thereto, and the pH of the mixed solution is adjusted to 7.5 with a 0.1 mol / L sodium hydroxide aqueous solution; then, after heating to 65°C, nitrogen is introduced for deoxygenation, and N,N-dimethylacrylamide and N-vinylpyrrolidone are added in sequence. After stirring for 1.5 hours, potassium persulfate is added to initiate the polymerization reaction, which is continued for 5 hours, and the reaction is stopped and cooled to room temperature; then, the reaction product is precipitated with acetone, and vacuum dried at 50°C, and the dried product is crushed to obtain the target product.
[0189] The high temperature resistant plugging and filtration reducer is a nanocellulose derivative, which is prepared from the following raw materials in parts by weight: 200 parts of 90% methanol aqueous solution, 150 parts of deionized water, 20 parts of nanocellulose crystals, 2 parts of vinyltrimethoxysilane, 2 parts of acrylamide, 3 parts of 2-acrylamide-2-methylpropanesulfonic acid, 0.06 parts of acetic acid, and 0.06 parts of ammonium persulfate;
[0190] The above-mentioned method for preparing the nanocellulose derivative comprises the following steps:
[0191] First, vinyltrimethoxysilane and acetic acid were added to a four-necked round-bottom flask filled with 90% (v / v) methanol aqueous solution, and then the temperature was slowly raised to 55°C under stirring conditions, and the hydrolysis reaction was carried out for 5 hours; then nanocellulose crystals were slowly added, and the temperature was raised to 80°C while stirring continuously. After the reaction was carried out for 21 hours, the heating was stopped and the product was cooled to room temperature; the solvent was removed by centrifugation, and the product was washed with anhydrous methanol for several times, and then vacuum dried to obtain the intermediate product;
[0192] Secondly, deionized water, acrylamide and 2-acrylamide-2-methylpropanesulfonic acid were added to a four-necked round-bottom flask in sequence, and the pH was adjusted to 7.5 with a 0.1 mol / L sodium hydroxide aqueous solution and stirred for 25 minutes; then, the intermediate product obtained in the above step was added thereto under stirring, nitrogen was passed for deoxygenation, the temperature was raised to 68°C, and ammonium persulfate was added to initiate the polymerization reaction, which lasted for 4 hours, then the reaction was stopped and cooled to room temperature; then, the mixture was washed with distilled water for multiple times, vacuum filtered, vacuum dried and crushed, and the obtained product was a nanocellulose derivative.
[0193] The high temperature resistant dispersion inhibitor is a tannic acid derivative, which is prepared from the following raw materials in parts by mass: 200 parts of 90% (v / v) ethanol aqueous solution, 150 parts of deionized water, 50 parts of tannic acid, 2.5 parts of γ-methacryloxypropyltriethoxysilane, 3.5 parts of allylamine, 4 parts of methacrylamide, 6 parts of sodium styrene sulfonate, and 0.12 parts of 2,2'-azobisisobutylamidine dihydrochloride;
[0194] The above-mentioned method for preparing tannic acid derivatives comprises the following steps:
[0195] First, γ-methacryloxypropyltriethoxysilane was added to a four-necked round-bottom flask filled with 90% (v / v) ethanol aqueous solution, and the pH was adjusted to 3.5 with citric acid, and then the temperature was slowly raised to 50°C under stirring conditions, and the hydrolysis reaction was carried out for 3 hours; then tannic acid was slowly added, and the temperature was continuously raised to 72°C with stirring, and the heating was stopped after the reaction for 17 hours, and the solution was cooled to room temperature; the solvent was removed by centrifugation, and the solution was washed with anhydrous ethanol for multiple times, and then vacuum dried and crushed to obtain an intermediate product;
[0196] Secondly, the intermediate product is added into a four-necked round-bottom flask filled with deionized water, and the pH is adjusted to 7.5 with 0.1 mol / L sodium hydroxide solution. After stirring for 30 minutes, allylamine, methacrylamide and sodium styrene sulfonate are added in sequence, nitrogen is passed to deoxygenate, and after heating to 68°C, 2,2'-azobisisobutylamidine dihydrochloride is added to initiate the polymerization reaction, which lasts for 3.5 hours. After the reaction is completed, it is cooled to room temperature, and a tannic acid derivative is obtained by washing, drying and crushing.
[0197] The lubricant is a mixture of 83 parts of liquid lubricant and 17 parts of solid lubricant, calculated by mass; wherein, the liquid lubricant is a mixture of 40 parts of polydimethylsiloxane, 20 parts of trimethylolpropane esterified rapeseed oil, 25 parts of phosphated palm oil and 15 parts of polyoxyethylene laurate, calculated by mass; the solid lubricant is a mixture of 30 parts of molybdenum disulfide micropowder, 40 parts of polytetrafluoroethylene micropowder, 20 parts of boron nitride micropowder and 10 parts of carbon nanotubes.
[0198] The density of the drilling fluid in this embodiment is 2.30 g / cm 3 The hot rolling temperature of the drilling fluid is 175℃. Example 5
[0199] This embodiment provides a high-temperature, high-density silicate water-based drilling fluid, which is composed of the following components in parts by weight:
[0200] Fresh water: 100 parts
[0201] Sodium bentonite: 1.5 parts
[0202] pH adjuster: 4.0 parts
[0203] Silicate: 4.0 parts
[0204] Silicate stabilizer: 5.0 parts
[0205] High temperature rheology modifier: 0.15 parts
[0206] High temperature resistant plugging and filtration reducer: 6.0 parts
[0207] High temperature resistant dispersion inhibitor: 3.0 parts
[0208] Lubricant: 3.0 parts
[0209] Barite: Add to drilling fluid to a density of 2.30 g / cm 3 .
[0210] Wherein, the pH regulator is a mixture of 40 parts of potassium hydroxide, 35 parts of magnesium oxide and 25 parts of magnesium hydroxide by mass fraction;
[0211] The silicate is a mixture of 55 parts of potassium silicate (modulus 3.05), 25 parts of potassium methyl silicate and 20 parts of potassium phenyl silicate, by mass;
[0212] The silicate stabilizer is a mixture of 30 parts of potassium citrate, 40 parts of potassium ethylenediaminetetramethylenephosphonate, 20 parts of potassium hydroxyethylidene diphosphonate and 10 parts of potassium diethylenetriaminepentamethylenephosphonate by mass;
[0213] The high temperature resistant rheology modifier is a diutan gum graft copolymer, which is prepared from the following raw materials in parts by weight: 100 parts of deionized water, 2 parts of diutan gum, 1.5 parts of N,N-dimethylacrylamide, 2.5 parts of N-vinylpyrrolidone, 1.5 parts of 2-acryloyloxybutylsulfonic acid, and 0.04 parts of potassium persulfate;
[0214] The preparation method of the diutan gum graft copolymer comprises the following steps:
[0215] First, deionized water is heated to 50°C, and then diutanol is slowly added under stirring. After it is fully dissolved, the diutanol aqueous solution is transferred to a four-necked round-bottom flask, 2-acryloxybutylsulfonic acid is added thereto, and the pH of the mixed solution is adjusted to 8 with a 0.1 mol / L sodium hydroxide aqueous solution; then, after heating to 75°C, nitrogen is introduced for deoxygenation, and N,N-dimethylacrylamide and N-vinylpyrrolidone are added in sequence. After stirring for 1 hour, potassium persulfate is added to initiate the polymerization reaction, which is continued for 4 hours, and the reaction is stopped and cooled to room temperature; then, the reaction product is precipitated with acetone, and vacuum dried at 50°C, and the dried product is crushed to obtain the target product.
[0216] The high temperature resistant plugging and filtration reducer is a nanocellulose derivative, which is prepared from the following raw materials in parts by weight: 200 parts of 90% (v / v) methanol aqueous solution, 150 parts of deionized water, 10 parts of nanocellulose crystals, 3 parts of vinyltrimethoxysilane, 1 part of acrylamide, 4 parts of 2-acrylamide-2-methylpropanesulfonic acid, 0.08 parts of acetic acid, and 0.07 parts of ammonium persulfate;
[0217] The above-mentioned method for preparing the nanocellulose derivative comprises the following steps:
[0218] First, vinyltrimethoxysilane and acetic acid were added to a four-necked round-bottom flask filled with 90% (v / v) methanol aqueous solution, and then the temperature was slowly raised to 55°C under stirring conditions, and the hydrolysis reaction was carried out for 5 hours; then nanocellulose crystals were slowly added, and the temperature was raised to 78°C while stirring continuously. After the reaction was carried out for 18 hours, the heating was stopped and the product was cooled to room temperature; the solvent was removed by centrifugation, and the product was washed with anhydrous methanol for several times, and then vacuum dried to obtain the intermediate product;
[0219] Secondly, deionized water, acrylamide and 2-acrylamide-2-methylpropanesulfonic acid were added to a four-necked round-bottom flask in sequence, and the pH was adjusted to 7.5 with a 0.1 mol / L sodium hydroxide aqueous solution and stirred for 20 minutes; then, the intermediate product obtained in the above step was added thereto under stirring, nitrogen was passed for deoxygenation, the temperature was raised to 66°C, and ammonium persulfate was added to initiate the polymerization reaction, which lasted for 5.5 hours, then the reaction was stopped and cooled to room temperature; then, the mixture was washed with distilled water for multiple times, vacuum filtered, vacuum dried and crushed, and the obtained product was a nanocellulose derivative.
[0220] The high temperature resistant dispersion inhibitor is a tannic acid derivative, which is prepared from the following raw materials in parts by mass: 200 parts of 90% (v / v) ethanol aqueous solution, 150 parts of deionized water, 70 parts of tannic acid, 3.5 parts of γ-methacryloxypropyltriethoxysilane, 4.5 parts of allylamine, 4 parts of methacrylamide, 7 parts of sodium styrene sulfonate, and 0.15 parts of 2,2'-azobisisobutylamidine dihydrochloride;
[0221] The above-mentioned method for preparing tannic acid derivatives comprises the following steps:
[0222] First, γ-methacryloxypropyltriethoxysilane was added to a four-necked round-bottom flask filled with 90% (v / v) ethanol aqueous solution, and the pH was adjusted to 4.5 with citric acid, and then the temperature was slowly raised to 50°C under stirring conditions, and the hydrolysis reaction was carried out for 3 hours; then tannic acid was slowly added, and the temperature was continuously raised to 73°C with stirring, and the heating was stopped after the reaction for 18 hours, and the solution was cooled to room temperature; the solvent was removed by centrifugation, and the solution was washed with anhydrous ethanol for multiple times, and then vacuum dried and crushed to obtain an intermediate product;
[0223] Secondly, the intermediate product is added into a four-necked round-bottom flask filled with deionized water, and the pH is adjusted to 8 with 0.1 mol / L sodium hydroxide solution. After stirring for 30 minutes, allylamine, methacrylamide and sodium styrene sulfonate are added in sequence, nitrogen is passed to deoxygenate, and after heating to 70°C, 2,2'-azobisisobutylamidine dihydrochloride is added to initiate the polymerization reaction, which is continued for 4 hours. After the reaction is completed, the mixture is cooled to room temperature, and a tannic acid derivative is obtained by washing, drying and crushing.
[0224] The lubricant is a mixture of 86 parts of liquid lubricant and 14 parts of solid lubricant, calculated by mass; wherein, the liquid lubricant is a mixture of 30 parts of polydimethylsiloxane, 30 parts of trimethylolpropane esterified rapeseed oil, 15 parts of phosphated palm oil and 25 parts of polyoxyethylene laurate, calculated by mass; the solid lubricant is a mixture of 40 parts of molybdenum disulfide micropowder, 30 parts of polytetrafluoroethylene micropowder, 10 parts of boron nitride micropowder and 20 parts of carbon nanotubes.
[0225] The density of the drilling fluid in this embodiment is 2.30 g / cm 3 The hot rolling temperature of the drilling fluid is 200℃. Comparative Example 1
[0226] The polysulfonated water-based drilling fluid commonly used on site is composed of 100 parts of fresh water, 3 parts of bentonite, 1.0 parts of pH regulator (the mass ratio of sodium hydroxide and sodium carbonate is 1:1), 5 parts of potassium chloride, 0.5 parts of zwitterionic polymer strong coating agent, 0.3 parts of low-viscosity carboxymethyl cellulose, 3 parts of sulfonated lignite resin, 3 parts of sulfonated asphalt, 3 parts of sulfonated phenolic resin, 3 parts of sulfonated tannin, 3 parts of modified vegetable oil, and barite is added to a density of 2.30 g / cm 3 .
[0227] The hot rolling temperature of the drilling fluid in this comparative example is 200°C.
[0228] The drilling fluids obtained in the above Examples 1-5 and Comparative Example 1 were evaluated according to GB / T16783.1-2014 "Field Test of Drilling Fluids in the Petroleum and Natural Gas Industry Part 1: Water-Based Drilling Fluids", and the results are shown in Table 1.
[0229] Table 1 Comprehensive properties of drilling fluids obtained in Examples 1-5 and Comparative Example 1
[0230]
[0231] Note: ρ: drilling fluid density, g / cm 3
[0232] T: Drilling fluid aging temperature, °C
[0233] t: Drilling fluid rolling aging time, h
[0234] PV: drilling fluid plastic viscosity, mPa·s
[0235] YP: Drilling fluid dynamic shear force, Pa
[0236] API: Drilling fluid medium pressure loss (0.7MPa, room temperature, 30min), mL
[0237] HTHP: Drilling fluid high temperature and high pressure filtration loss (3.5MPa, T, 30min), mL
[0238] PPT: Drilling fluid permeate loss (6.9MPa, T, 30min), mL
[0239] pH: pH value of drilling fluid filtrate, dimensionless
[0240] EP: Extreme pressure friction coefficient, dimensionless
[0241] CRR: Shale rolling recovery rate, %
[0242] SSR: shale strength retention rate (3.5MPa, T, 72h), %.
[0243] It can be seen from Table 1 that in Examples 1 to 5, the high-temperature and high-density silicate water-based drilling fluid has a density of 1.80 to 2.30 g / cm 3 range, the temperature is in the range of 150~200℃, and after 24 hours of aging, they all have good rheological properties, filtration performance, plugging performance, lubrication performance, inhibition performance and anti-collapse performance. It can be seen from Example 5 and Comparative Example 1 that compared with the commonly used polysulfonated water-based drilling fluid on site, the high-temperature and high-density silicate water-based drilling fluid has a more stable rheology and shows better suspension rock carrying performance; and the HTHP filtration loss and PPT percolation are smaller, showing more significant plugging and filtration loss reduction performance; at the same time, the extreme pressure friction coefficient is lower, the shale rolling recovery rate is higher, and better lubrication and inhibition performance are shown. The most critical thing is that the high-temperature and high-density silicate water-based drilling fluid performs better in anti-collapse performance, and the strength retention rate of shale after being soaked in it at high temperature and high pressure for 72 hours is more than 95.0%; while for the commonly used polysulfonated water-based drilling fluid on site, the strength retention rate of shale after soaking in it for the same time is only 20.7%.
[0244] The five groups of embodiments of the high-temperature and high-density silicate water-based drilling fluid of the present invention, after aging for 24 hours at different densities and different temperatures: pH>11, ensuring the stability of silicate; good rheological properties, dynamic shear force not less than 8Pa, showing good suspension rock carrying performance; low HTHP filtration loss, generally not exceeding 11.6mL; excellent PPT plugging performance, which is beneficial to reducing the penetration of filtrate into the formation and preventing the well wall from becoming unstable; the extreme pressure friction coefficient is not higher than 0.1, the lubrication performance is good, which is beneficial to reducing friction torque and improving the mechanical drilling speed; the shale rolling recovery rate generally exceeds 100%, this is because the silicate adsorbed on the shale surface not only ensures the integrity of the cuttings but also increases the quality of the recovered cuttings, which fully demonstrates that the high-temperature and high-density silicate water-based drilling fluid has excellent shale inhibition performance; the shale strength retention rate is not less than 95.6%, the anti-collapse effect is significant, which is beneficial to stabilizing the shale well wall and ensuring safe and efficient drilling operations in deep shale formations.
[0245] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-temperature, high-density silicate water-based drilling fluid, characterized in that: The raw materials include, by mass, 100 parts of water, 1.0-2.0 parts of bentonite, 3.0-5.0 parts of pH regulator, 3.0-5.0 parts of silicate, 3.0-5.0 parts of silicate stabilizer, 0.1-0.3 parts of high temperature rheology regulator, 4.0-6.0 parts of high temperature plugging and filtration reducer, 2.0-3.0 parts of high temperature dispersion inhibitor, 2.0-4.0 parts of lubricant and barite; the barite is not limited in the number of parts, and the density of the silicate water-based drilling fluid added is 1.80-2.30 g / cm 3 ; The silicate is composed of 40-60 parts of potassium silicate, 20-30 parts of methyl potassium silicate and 20-30 parts of phenyl potassium silicate; The high temperature resistant rheology modifier comprises the following raw materials in parts by weight: 100 parts of water, 1 to 3 parts of diutan gum, 1 to 3 parts of N, N-dimethylacrylamide, 2 to 5 parts of N-vinyl pyrrolidone, 0.5 to 1.5 parts of 2-acryloyloxybutyl sulfonic acid and 0.02 to 0.05 parts of potassium persulfate; The high temperature resistant plugging and fluid loss reducer comprises the following raw materials in parts by mass: 200 parts of methanol aqueous solution, 150 parts of water, 10-20 parts of nanocellulose crystals, 2-5 parts of vinyltrimethoxysilane, 1-3 parts of acrylamide, 3-5 parts of 2-acrylamide-2-methylpropanesulfonic acid, 0.05-0.10 parts of acetic acid and 0.05-0.08 parts of ammonium persulfate; The high temperature resistant dispersion inhibitor comprises the following raw materials in parts by mass: 200 parts of ethanol aqueous solution, 150 parts of water, 40-80 parts of tannic acid, 2-4 parts of γ-methacryloxypropyltriethoxysilane, 3-5 parts of allylamine, 4-6 parts of methacrylamide, 5-8 parts of sodium styrene sulfonate and 0.10-0.16 parts of 2,2'-azobisisobutylamidine dihydrochloride; The silicate stabilizer is at least one of potassium citrate, potassium ethylenediaminetetramethylenephosphonate, potassium hydroxyethylidene diphosphonate and potassium diethylenetriaminepentamethylenephosphonate; The preparation method of the high temperature resistant rheology regulator comprises the following steps: Dissolving diutan gum in water to obtain a diutan gum aqueous solution; Adding 2-acryloyloxybutylsulfonic acid to the diutanol aqueous solution and adjusting the pH to alkaline to obtain a mixed solution I; The mixed solution I is heated, and then N,N-dimethylacrylamide and N-vinylpyrrolidone are added in sequence under an inert atmosphere, stirred evenly, and then potassium persulfate is added to initiate a polymerization reaction, thereby obtaining the high temperature resistant rheology regulator; The preparation method of the high temperature resistant plugging fluid loss reducer comprises the following steps: Vinyltrimethoxysilane and acetic acid are added to a methanol aqueous solution to carry out a hydrolysis reaction. After the hydrolysis reaction is completed, nanocellulose crystals are added to the hydrolyzate to carry out a heating and stirring reaction to obtain an intermediate product A. Mix water, acrylamide and 2-acrylamide-2-methylpropanesulfonic acid and adjust the pH to alkaline to obtain a mixed solution II; Stirring the mixed solution II, then adding the intermediate product A to the mixed solution II under stirring conditions, and then adding ammonium persulfate under the protection of an inert atmosphere to initiate a polymerization reaction, thereby obtaining the high temperature resistant plugging and filtration reducer; The preparation method of the high temperature resistant dispersion inhibitor comprises the following steps: γ-methacryloxypropyltriethoxysilane is added to an ethanol aqueous solution, and then a hydrolysis reaction is carried out under acidic conditions. After the hydrolysis reaction is completed, tannic acid is added to the hydrolysis solution, and a heating and stirring reaction is carried out to obtain an intermediate product B; After dissolving the intermediate product B in water, adjusting the pH to alkaline to obtain an aqueous solution of the intermediate product B; The aqueous solution of the intermediate product B is stirred, and then allylamine, methacrylamide and sodium styrene sulfonate are added in sequence, and then 2,2'-azobisisobutylamidine dihydrochloride is added under the protection of an inert atmosphere to initiate a polymerization reaction to obtain the high temperature resistant dispersion inhibitor.
2. The high-temperature and high-density silicate water-based drilling fluid according to claim 1, characterized in that: The pH adjuster is at least one of potassium hydroxide, magnesium oxide and magnesium hydroxide.
Citation Information
Patent Citations
Potassium metasilicate polymeric alcohol water base drilling fluid
CN102391843A
High temperature resistant silicate drilling fluid for steady well wall in deep well
CN1504527A
Lubricant for drilling fluid
CN105368410A
Organic-inorganic composite silicate high-temperature-resistant film-forming drilling fluid system
CN109735314A